2019
DOI: 10.1002/ente.201800694
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Kinetics and Activity of Ni‐Based Catalysts for Benzyl Phenyl Ether Catalytic Hydrogenolysis

Abstract: The influence of the type of support [activated carbon (AC), HZSM‐5, and γ‐Al2O3] on the performance of Ni‐based catalysts for the catalytic hydrogenolysis (CH) of benzyl phenyl ether (BPE) is investigated. The properties of an Ni‐based catalyst are investigated using diverse characterization techniques. An Ni/AC catalyst exhibits the highest dispersion of Ni atoms by CO pulse. The kinetic studies show that the apparent activation energies (Ea) for CH of BPE increase in the order Ea (Ni/AC) < Ea (Ni/γ‐Al2O3) <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…The result revealed that the hydrogen source was mainly provided by H 2 . The literature reported Ni/AC selectively cleaved BPE under a H 2 atmosphere with a conversion of 22% but no conversion under an Ar atmosphere at 120 °C and 40 min, which was well consistent with the experiment result.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The result revealed that the hydrogen source was mainly provided by H 2 . The literature reported Ni/AC selectively cleaved BPE under a H 2 atmosphere with a conversion of 22% but no conversion under an Ar atmosphere at 120 °C and 40 min, which was well consistent with the experiment result.…”
Section: Resultssupporting
confidence: 91%
“…The hydrogen donor from H 2 and isopropanol was used for catalytic hydrogenolysis of DPE over Ni/AC-3. The hydrogen donor provided H•, and abundant H• adsorbed and activated on the Ni surface to form Ni–H to promote the hydrogenolysis of DPE. , Meanwhile, water produced by the dehydration of isopropanol over Ni/AC-3 led to the hydrolysis of a small amount of DPE. Isopropanol played a significant role in this catalytic reaction.…”
Section: Resultsmentioning
confidence: 99%
“…The crystal structure of Al 2 O 3 is not affected by the loading of Ni. Peaks at 2θ of 37.60° and 66.76° are the characteristic diffraction peak of γ‐Al 2 O 3 and the peaks at 2θ of 44.51°, 51.85° and 76.37° are attributed to the metallic nickel phase . The peaks of Ni are not detected on 1Ni/Al 2 O 3 due to the small crystallinity or highly dispersed of Ni.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, Ni is the most used due to its relatively low cost and considerable catalytic activity. Work in this area aims at optimizing the hydrogenolysis of the CÀ O bonds connecting the aromatic rings, [20][21][22][23][24][25][26][27][28][29] keeping the hydrogenation of phenol as low as possible.…”
Section: Introductionmentioning
confidence: 99%